2020
DOI: 10.1016/j.jemep.2020.100581
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence de l’hypertension artérielle et les facteurs de risques en milieu professionnel en République démocratique du Congo : cas de la société textile de Kisangani

Abstract: Résultats. -La prévalence de l'HTA était de 32,5 %. Les facteurs significativement associés à l'HTA étaient le sexe [OR = 2,2] ; l'âge (> 54 ans [OR = 22] ; l'excès pondéral (obésité [OR = 4,3] et l'inactivité physique [OR = 2,3]. Le stress [OR = 2,4], les antécédents de l'HTA dans la fratrie [OR = 2,4] ainsi la connaissance de prévention sur l'HTA [OR = 1,2] étaient également associés à l'HTA. Par contre, le statut à l'emploi [OR = 0,5] était négativement associé à l'HTA.Conclusion. -Ce travail révèle une for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A length of service of more than 5 years in the cotton sector has also been associated with hypertension. This result is similar to that of Panda et al 21 , who found an increase in risk according to seniority in the textile sector in Congo in a bivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A length of service of more than 5 years in the cotton sector has also been associated with hypertension. This result is similar to that of Panda et al 21 , who found an increase in risk according to seniority in the textile sector in Congo in a bivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of hypertension in this study is similar to that observed in the general population of Benin. However, it is lower than the 32.5% and 49.3% achieved respectiveley by Panda et al 21 in a textile company in Congo in 2020, and by Ngombe et al 29 in flour mills in Lubumbashi in Congo in 2015. Meanwhile, the prevalence in our study is higher than that of Dia et al 22 obtained in a study conducted in an aluminum processing company in Cameroon.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations